Modificación de acciones penales en relación a la trata de personas en niños, niñas y adolescentes en el Ecuador - Elizalde Robles, Nery David (2017)
he research had as general objective "Analyze standards of the Code Integral Criminal (COIP), its interpretation and application to determine which aspects and phases should suggest change to the appropriate punishment to the perpetrators and prevent impunity, this research there was the analysis and synthesis, based on the inductive method where studier particular aspects to reach a general analysis; and deductive method will allow us to analyze general aspects to reach particular conclusions, for field research surveys apply 30 professionals free exercise law, authorities of educational institutions and individuals. For the realization of the objectives; General will link theory with practice, the specific objectives by collecting extracted from existing literature sources, the information gathered from the empirical sources of information, both general and specific objectives will check with the field research. The data obtained are presented in statistical tables with their analysis. Having analyzed the theoretical framework and the results of the implementation of surveys effected, the conclusions the same as we get development work in the same way it came to recommendations for personnel involved and the competent authorities. Given that is a modification of criminal proceedings it is important to make a proposal to help change laws to prevent impunity for traffickers especially children and adolescents.